BREEDING BEHAVIOUR OF RED-WATTLED LAPWING, VANELLUS INDICUS (BODDAERT, 1783) IN AGRICULTURAL LANDSCAPE OF PUNJAB - KUMAR, CHARN; THIND, SANDEEP KAUR; JOSHUA, .; KALEKA, AMRITPAL SINGH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
During the breeding seasons 2017-2019, breeding behaviour of the Red-wattled Lapwing (RL), Vanellus indicus was studied in agricultural fields and non-agricultural nesting grounds located in the northern rural and semi-urban outskirts of Khanna city in Punjab. Observations on nest structure, egg laying, incubation, hatching and other behavioural aspects of the parents/chicks were inferred from video-records, photographs and direct field observations made on 35 clutches containing 117 eggs. In the study area the breeding season extended from April to July and the mean value of the nest structure parameters namely, outer diameter, inner diameter and depth were 21±3.02 cm, 12.08±1.13 cm and 3.05±0.63 cm respectively. The mean clutch size was 3.34±0.81 (range 1-4) and it differed between the agricultural field clutches (2.91±0.94, range: 1-4) and non-agricultural sites (3.54±0.66, range: 2-4). The egg length, breadth, initial weight, egg shape index and volume measured 42.08±1.20 cm, 30.21±0.80 cm, 19.44±1.15 gm, 71.85±2.79 and 17.56±1.04 cm3 respectively. The incubation period varied from 27 to 30 days (n=12) with a mean value of 28.75±0.97 days. A review of the video records spanning 64.55 hours total observation time (TOT) recorded over 06 days of full incubation including the hatching day revealed that the RL parents spent 58.8 hours (91.09% TOT) and 5.75 hours (8.91% TOT) as attentive periods and inattentive periods respectively. Synchronous hatching was completed in one or two successive days (within 24 hours) in 18 clutches/61 eggs and two three-egged hatched asynchronously over three days. Further, the continuous video records made during the present study revealed that the minimum interval between two successive hatching may be as short as 1.72 hours. The newly hatched chick weighed on average 13.65 gm (n=4). A comparison of the hatching success calculated as per the Mayfield Method revealed that it was only 6.90% in agricultural field sites and 64.80% in non-agricultural sites (sparsely grassy vacant plots, low grassy lawns/grounds, cattle dung heaps and rooftops).